PENINGKATAN KUALITAS KEHIDUPAN KERJA MELALUI ANALISIS STRESS KERJA SERTA FAKTOR YANG MEMPENGARUHI (Studi pada Anggota Dit. Reskrimum POLDA Jateng) - Pratiwi, Maharani Ayu (Master of Management Diponegoro University, 2014)
control in a variety of human behavior. Although the police do their job fair, good, and theywork diplomatically still not an easy task. Police in carrying out his responsibilities as a lawenforcement and justice has several tasks, namely as a patrol officer, detective, juvenilepolice, traffic police, officer training, officer identification, and laboratory personnel (crime).The phenomenon encourages research that examine how to improve the quality of workinglife member of the Dit. Reskrimum Central Java Police.The model was developed to answer the research problem consists of four variables thatinclude the variable characteristics of the organization and job characteristics as exogenousvariables as well as the job stress and quality of work life as an endogenous variable thatproduced five research hypotheses. Data on the variables obtained through interview usingquestionnaires to 106 members of the DIT. Reskrimum Central Java Police. The collecteddata is then analyzed by using SEM.Statistical test results showed that the statistical characteristics of the organization provedpositive and significant effect on Job Stress, Job Characteristics proved statistically significantand positive effect on Job Stress, Job Stress has not been proven statistically significanteffect on Quality of Life Work, Organizational Characteristics statistically proven effect positiveand significant impact on quality of work life and job characteristics are statistically provenpositive and significant impact on the Quality of Work Life.